DECISION SUPPORT SYSTEM FOR SELECTION OF PESTICIDES FOR CHILI PLANTS USING THE MABAC METHOD - Sukamto, Sukamto; Fitriansyah, Aidil; Nugrah, Randi Andri (Informatika, Universitas Jenderal Soedirman, 2023)
The use of pesticides in agriculture plays a role in preventing and reducing diseases in chili plants. Pesticides for chili plants are quite widely spread on the market and have the advantages of each product offered to farmers, so farmers must be more careful and understanding in choosing pesticides to be used in preventing chili plant diseases. For that we need a decision support system (SPK). The data used in this research are 10 types of pesticides as an alternative. While the criteria are determined based on the agriculture and food service, namely price, classification, number of diseases eradicated, method of action, shelf life, and formulation concentration. Data analysis uses the MABAC method to support decision making for farmers in providing an assessment of the best pesticides on chili plants by steps to forming decision matrices, normalizing decision matrices, determining weighted matrices, determining border area matrices, determining alternative distance matrices, and ranking. The research results obtained the three best pesticides are Tridex 80 WP, Ziflo 76 WG, and Cabriotop 60 WG.